ROLE OF APELIN/MONOCYTE CHEMOATTRACTANT PROTEIN-1, INFLAMMATORY, APOPTOTIC MARKERS IN THE REGULATION OF PATIENTS WITH NON-ALCOHOLIC FATTY LIVER DISEASE - Youness, Eman R; Aly, Hanan Farouk; Nemr, M El (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to investigate blood nuclear factor ÎºB (NF-ÎºB), apelin, Lipid peroxide product ; thiobarbituric acid (TBA) malonaldehyde (MDA), monocyte chemoattractant protein-1 (MCP-1), B-cell lymphoma 2 (Bcl2), and paraoxonase (PON1) levels in patients with non -alcoholic fatty liver disease (NAFLD) in a trail to correlate the significance of these biomarkers in the diagnosis and initiation of NAFLD patients. Methods: A total of 32 patients with NAFLD and 45 healthy controls were enrolled in the study. Apelin levels were measured along with, NF-ÎºB, MCP1, MDA, Bcl2, and PON1 were detected. Results: Significant increase in serum NF-ÎºB, MDA, MCP1, and apelin levels in NAFLD patients with percentages increase 1031.23, 293.02, 165.93, and 120 %, respectively, while significant reduction in PON1 and BCl2 with percentages decrease 54.58 and 79.03 %, respectively, were detected as compared to controls. A significant correlation was found between serum concentration of the measured biomarkers with the incidence of NAFLD. Conclusions: It could be concluded that the patients with NAFLD have significantly increased circulating apelin, NF-ÎºB, and MDA levels as compared to healthy control subjects while significant reduction in BCl2 and PON1 levels were recorded. Besides, the NAFLD status is tightly attributed to the existence of insulin resistance and oxidative stress.